Conflict Between Hizb Ut-Tahrir And Islamic Civil Society In Indonesia:A Countermovement Approach - Hasbi Aswar; Danial Bin Mohd. Yusof; Rohana Binti Abdul Hamid (Program Studi Hukum Tata Negara, Fakultas Syariah dan Hukum Islam IAIN Bone, 2020)
In a social movement study, countermovement emerges when certain movement is considered to bring threat to the status quo or the current political and social condition. Social movement seeks for changing the existing situation while the countermovement pursues to keep it. As a result, the conflict between two becomes inevitable, where both will compete to win over the other. The existence of Hizb ut-Tahrir in Indonesia (HTI) for years is responded by some Islamic groups especially Nahdlatul Ulama (NU) and its allies, as threat to the Indonesian life due to the idea brought by HTI. It becomes the root of conflict between HTI and other Islamic groups in Indonesia. This article aims to explain the conflict between HTI and other Islamic groups by elaborating the effort of the Islamic groups to counter the HTI narratives and mobilization by using countermovement approach in social movement studies. This article is a case study research and using mainly secondary data to analyze the issue. This article found that Nahdlatul Ulama as the main countermovement played significant role to counter Hizb ut-Tahrir`s religious and political narratives as well as its political mobilization.